Clinical Oral Investigations Biological and Physicochemical Characterization of Nanoemulsions Containing Morin and its Derivatives for Endodontic Purposes - Pereira, Jesse Augusto [UNESP]; Rios, Rafael Araújo [UNESP]; Duarte, Jonatas Lobato [UNESP]; Moraes, Graciele Ribeiro [UNESP]; Ramos, Ana Paula; Guiotti, Aimée Maria [UNESP]; Kishen, Anil; Regasini, Luís Octavio [UNESP]; Chorilli, Marlus [UNESP]; Duque, Cristiane [UNESP] (Springer Nature, 2025)
Objectives
Considering the lack of medications with a wide range of therapeutic effects for the endodontic treatment of immature teeth, this study aimed at synthesizing two morin (Mo) derivatives and testing their cytotoxicity and effect on multispecies biofilm in solution and loaded in nanoemulsions (NE).
Material and methods
Minimum inhibitory and bactericidal concentration (MIC/MBC) of Mo, penta-acetylated Mo (Ac-Mo), Mo complexed with strontium (Sr-Mo) and control chlorhexidine (CHX) were determined against some oral bacteria. NE were physiochemically characterized by analysis of particle size, polydispersity index and zeta potential. NE containing Mo, its derivatives and CHX were evaluated against multispecies biofilms by bacterial counts, scanning electron microscopy and confocal microscopy. The cytotoxicity of the compounds and NE was also determined in fibroblasts using resazurin assays. The data were statistically evaluated (p < 0.05).
Results
All compounds presented bactericidal action against all bacteria tested (MIC/MBC from 0.125 to 1 mg/mL). Metabolic activity of fibroblasts was higher than 70% after treatment with compounds at 0.25mg/mL or lower. NE showed good droplet size distribution in nanoscale and stability. The highest bacterial reduction in multispecies biofilms was observed in NE + Ac-Mo, followed by NE + Mo, CHX and NE + Sr-Mo groups. All NE diluted at 12.5% did not affect fibroblast metabolism after 24h of treatment.
Conclusions
Morin and its derivatives, either alone or loaded in nanoemulsions, were effective against oral bacteria and showed cytocompatibility at lower concentrations.
Clinical Relevance:
Nanoemulsion containing penta-acetylated morin could be an alternative intracanal medication for reducing residual bacteria between clinical appointments in regenerative endodontic approaches for immature teeth.